2014
DOI: 10.1142/s0218127414501284
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Design and Circuit Implementation of Integer Domain Chaotic Systems

Abstract: In this paper, a new approach for constructing integer domain chaotic systems (IDCS) is proposed, and its chaotic behavior is mathematically proven according to the Devaney's definition of chaos. Furthermore, an analog-digital hybrid circuit is also developed for realizing the designed basic IDCS. In the IDCS circuit design, chaos generation strategy is realized through a sample-hold circuit and a decoder circuit so as to convert the uniform noise signal into a random sequence, which plays a key role in circui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The circuit realization is important for the chaotic system, especially by adopting commercially common electronic components [28][29][30]. In this section, we build an electronic circuit to physically realize the reported system for different cases, based on the improved module-based technique 7 Complexity [31][32][33][34]. The electronic circuit is designed as the jerk form by using the dimensionless state equations, as depicted in Figure 12, which is simple with less circuit elements.…”
Section: Circuit Realization Of a Memristor-based Jerk Systemmentioning
confidence: 99%
“…The circuit realization is important for the chaotic system, especially by adopting commercially common electronic components [28][29][30]. In this section, we build an electronic circuit to physically realize the reported system for different cases, based on the improved module-based technique 7 Complexity [31][32][33][34]. The electronic circuit is designed as the jerk form by using the dimensionless state equations, as depicted in Figure 12, which is simple with less circuit elements.…”
Section: Circuit Realization Of a Memristor-based Jerk Systemmentioning
confidence: 99%
“…Luo et al presented a homeomorphism and showed that an invertible mapping on a compact metric space was Li-Yorke chaotic [25]. Wang et al provided two chaotic systems satisfying Devaney's definition of chaos in [29,30]. In [38], Zheng et al solved the chaotic dynamical degradation problem in real domain by providing an effective schemes with symbolic dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…This is very different from the existing discrete-time chaotic system in infinite precision real number domain, that all bits will participate in all the update operations by the iterative function. Digital chaotic system constructed with the chaos generation strategy controlled by random sequences is proven to satisfy the Devaney's definition of chaos in [19], [20], [21], [22], [23], [24]. Since this system is directly generated in finite precision digital domain, there is no finite precision effect problem, and the binary sequences can be obtained without transformation and combination.…”
Section: Introductionmentioning
confidence: 99%
“…In [21], chaotic combination of two input entropic streams has solved flaws exhibited in the system designed in [20]. The chaos generation strategy was implemented in [22], through a sample-hold circuit and a decoder circuit so as to convert the uniform noise signal into a random sequence. The second chaos generation strategy named Chaotic Bitwise Dynamical System (CBDS) was proposed in [23].…”
Section: Introductionmentioning
confidence: 99%